Cross-Linguistic Word Recognition Development Among Chinese Children: A Multilevel Linear Mixed-Effects Modeling Approach - Guan, Connie Qun; Fraundorf, Scott H. (Frontiers in Psychology, 2020)
The effects of psycholinguistic variables on reading development are critical to the evaluation of theories about the reading system. Although we know that the development of reading depends on both individual differences (endogenous) and item-level effects (exogenous), developmental research has focused mostly on average-level performance, ignoring individual differences. We investigated how the development of word recognition in Chinese children in both Chinese and English is affected by (a) item-level, exogenous effects (word frequency, radical consistency, and curricular grade level) (b) subject-level, endogenous individual differneces (orthographic awareness and phonological awareness), and (c) their interactive effect. We tested native Chinese (Putonghua) speaking children (n=763) in grades 1 to 6 with both Chinese characters and English word identification (lexical) decision tasks. A multilevel linear mixed-effects modeling approach allows us to examine both in reduced models to compare the overall pattern of grade-level differences between Chinese and English directly, but also simultaneously examine both subject- and item-level differences, and the interaction effects within both languages among Chinese-English bilingual readers. Our findings show that (a) there are both effects of word frequency and age of acquisition in both Chinese and English, but these item-level effects generally weakened with increasing age, (b) individual differences in phonological and orthographic awareness each contributed to successful performance, (c) in Chinese, item-level effects were weaker for more proficient readers. We contend that our findings can be explained by theoretical models that incorporate cumulative learning as the basis for development of item-level effects in the reading system.